A gestão dos resíduos urbanos no município de Araguaína – TO. - Calhau, Maribel Sobral dos Santos (Universidade Federal do Tocantins, 2022)
Proper disposal of solid waste is a subject that must be discussed and practiced, Law 12.305 / 2010 establishes guidelines for its application. The mandatory creation of a landfill is one of its requirements, which aims to improve the environment and society. This research discusses the Management of Urban Solid Waste of the city Araguaína, where 145,000 kg of MSW are collected per day. This research is characterized as a case study, in which a questionnaire was applied to the inspector of the outsourced company responsible for the city's landfill. The answers obtained through the questionnaire contributed to update data, which were previously analyzed in bibliographic research. As a result, there is a replication of the RSW management in Araguaína, both from a theoretical and practical point of view. The city has already complied with Law 12.305 / 2010 and has a landfill that meets the established obligations.